Influence of diameter on flexural strength of fiberglass pins (Research, Society and Development, 2022)
Dental elements that have coronal destruction and are endodontically treated become more fragile. The use of intraradicular retainers has become a viable option for the rehabilitation of partially compromised teeth. The objective of this work was to evaluate whether the diameter of the posts presents similar flexural strength when compared to different commercial brands. Fiberglass posts (FGP) (n=05) of four brands (FGM, ANGELUS, INDUSBELLO and SUPERPOST) were selected, in the respective diameters 0.5; 1 and 2. The posts were subjected to a three-point bending test in a universal testing machine (EMIC - Mechanics Laboratory of the University Center of Patos de Minas-MG), with a span of 10.0 mm, speed of 0 .5 mm/min-1, with a cross-sectional diameter of 2 mm of the loading tip, with a load cell of 500 N. The Kruskal Wallis, Chi-Square and Dunnett statistical tests were used. The ANGELUS group presented the highest flexural resistance, in which a significant difference was observed compared to the SUPERPOST 0.5 group (p=0.001) and compared to the INDUSBELLO 2 group (p=0.015). There was a significant difference between the diameters within the same group ANGELUS 2 and ANGLEUS 0.5 (p